2005
DOI: 10.1056/nejmcps050929
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Hypothermia for Neonates with Hypoxic–Ischemic Encephalopathy

Abstract: Whole-body hypothermia reduces the risk of death or disability in infants with moderate or severe hypoxic-ischemic encephalopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
1,830
12
46

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,508 publications
(1,936 citation statements)
references
References 32 publications
48
1,830
12
46
Order By: Relevance
“…Four recent landmark prospective randomized-controlled studies showed that induced mild to moderate hypothermia improved neurologic function in patients suffering cardiac arrest from ventricular fibrillation (Hypothermia after Cardiac Arrest Study Group, 2002;Bernard et al, 2002) and reduced risk of death or disability in neonates hypoxic-ischemic encephalopathy (Gluckman et al, 2005;Shankaran et al, 2005). In the case of acute stroke treatment, temperature on admission correlates with neurologic outcome: hyperthermia is associated with poor prognosis (den Hertog et al, 2007;Krieger et al, 2005).…”
Section: Clinical Translation and Future Directionsmentioning
confidence: 99%
“…Four recent landmark prospective randomized-controlled studies showed that induced mild to moderate hypothermia improved neurologic function in patients suffering cardiac arrest from ventricular fibrillation (Hypothermia after Cardiac Arrest Study Group, 2002;Bernard et al, 2002) and reduced risk of death or disability in neonates hypoxic-ischemic encephalopathy (Gluckman et al, 2005;Shankaran et al, 2005). In the case of acute stroke treatment, temperature on admission correlates with neurologic outcome: hyperthermia is associated with poor prognosis (den Hertog et al, 2007;Krieger et al, 2005).…”
Section: Clinical Translation and Future Directionsmentioning
confidence: 99%
“…Finally, in the 1990s laboratory studies demonstrated the benefit of mild hypothermia in dogs after cardiac arrest [14]. In the last decade, pivotal randomized clinical trials have provided direct evidence of a benefit of mild hypothermia to improve neurological outcome after cardiac arrest and perinatal asphyxia [1,2,[4][5][6][7].…”
Section: Historical Aspectsmentioning
confidence: 99%
“…Until the last decade, management of a newborn with HIE had consisted largely of supportive care. In the last 6 years, 3 large, randomized, placebo-controlled trials have shown that TH initiated within 6 h of birth reduces death and disability in these infants [5][6][7].…”
Section: Perinatal Asphyxiamentioning
confidence: 99%
See 1 more Smart Citation
“…Brain swelling is an important problem in pediatric TBI, and hypothermia has been shown to reduce intracranial pressure in adult and pediatric patients and to reduce cerebral swelling in animal models [81,82]. Induced hypothermia has also been shown to decrease mortality and improve outcome in neonates with hypoxic-ischemic injury [83]. In addition, early unintentional hyperthermia is common in pediatric TBI and has been associated with worse outcomes [84].…”
Section: Hypothermiamentioning
confidence: 99%